Enhanced Cells Anchoring to Electrospun Hybrid Scaffolds With PHBV and HA Particles for Bone Tissue Regeneration - Karbowniczek, Joanna E.; Kaniuk, Łukasz; Berniak, Krzysztof; Gruszczyński, Adam; Stachewicz, Urszula (Frontiers in Bioengineering and Biotechnology, 2021)
Hybrid materials combining organic and inorganic compounds used as scaffolds are highly beneficial in bone regeneration. In this study, we successfully produced by blend electrospinning poly(3-hydroxybutyric acid-co-3-hydrovaleric acid) (PHBV) scaffolds enriched with hydroxyapatite (HA) particles to biomimic bone tissue for improved and faster regeneration processes. The morphology, fiber diameters, and composition of the scaffolds were investigated by scanning electron microscopy (SEM) techniques followed by focused ion beam (FIB) sectioning to verify HA particles integration with PHBV fibers. In vitro cell culture was performed up to 7 days and followed with the cell proliferation test (CellTiter-Blue® Assay). Additionally, cell integration with scaffold was visualized by confocal and SEM imaging. We showed a simple way of obtaining hybrid scaffolds by electrospinning of PHBV solution with HA particles without any post-processing. The PHBV+HA scaffold enhanced cell proliferation and filopodia formation responsible for cells’ anchoring within the created 3D environment. The obtained results show the great potential in the development of hybrid scaffolds stimulating bone tissue regeneration.